Analysis of Efficiency Of KDT-OAT and Removal Preparations on The Recovery of Pulmonary Tuberculosis - Kristin Berlianta Duha; Sri Lestari Ramadhani Nasution; Ermi Girsang; Tan Suyono (International Journal of Health and Pharmaceutical (IJHP), 2022)
Background: Tuberculosis is one of the 10 most common causes of death and is the single most common cause of infection and causes illness every year in millions of people. The etiology of tuberculosis is the bacteria Mycobacterium tuberculosis and Mycobacterium bovis. These germs have a size of 0.5-4 microns x 0.3-0.6 microns with thin rods, straight or slightly bent, granular or have no sheath, but have a thick outer layer consisting of lipoids (especially mycolic acid). Based on data from the Riset Kesehatan Dasar in 2018 conducted by the Kementerian Kesehatan RI, the prevalence rate of pulmonary TB by doctors in Indonesia in 2018 was the same as in 2013 which was 0.4%. Based on the OAT guidelines used in Indonesia, there are two OAT drug preparations, namely OAT-KDT or (FDC) and the Kombipak package. Comparison of the efficacy of this drug in curing pulmonary TB also varies. Objective: To determine the efficacy of KDT-OAT and removal preparations on the cure rate of pulmonary TB. Methods: This type of research is a retrospective cohort study, which is a time-period approach. This study was conducted in October-November 2020. Results: There was no significant difference in treatment outcomes in pulmonary TB patients who received OAT-KDT or OAT-release preparations.